Figure 3 from Gene-Expression Profiling of Mucinous Ovarian Tumors and Comparison with Upper and Lower Gastrointestinal Tumors Identifies Markers Associated with Adverse Outcomes - Nicola S. Meagher (15048462) (2025)
Heat map of unsupervised clustering analysis. Contains all samples with a concordant pathology diagnosis (n = 497), with MOC grouped by FIGO stage. Labels show main clusters and diagnoses. Gene-expression values are normalized and logarithm base 2 transformed. dx, diagnosis.